If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(8y + -4) = 8y Reorder the terms: 2(-4 + 8y) = 8y (-4 * 2 + 8y * 2) = 8y (-8 + 16y) = 8y Solving -8 + 16y = 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -8 + 16y + -8y = 8y + -8y Combine like terms: 16y + -8y = 8y -8 + 8y = 8y + -8y Combine like terms: 8y + -8y = 0 -8 + 8y = 0 Add '8' to each side of the equation. -8 + 8 + 8y = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 8y = 0 + 8 8y = 0 + 8 Combine like terms: 0 + 8 = 8 8y = 8 Divide each side by '8'. y = 1 Simplifying y = 1
| 1x-1y=2 | | 100(.018x+0.09y)=100(360)(0.16) | | 2x^3+1x^2+8x= | | x^2+3xy-10y^2=0 | | 22=6+2d | | 8+3B=-1 | | -8(x+5)+7(2x+1)= | | -3/2(2y+6)=15 | | .018x+0.09y=(360)(0.16) | | 65x+300=47x | | r^2+3r-28= | | 1/2(x-11)=9 | | 2g-5=26 | | .06x+0.10y=(240)(0.08) | | 5k^2+6k-11=0 | | 5s^2-31s=28 | | 5k^2+16k-11=0 | | 5k^2+16k+11=0 | | 4x^9y^7+16x^7y^6+28xy= | | 5k^2-4k-1=0 | | (7x+3)=(4x+1) | | t^2-10t+21=0 | | 6x+13=43 | | 4=1i+0.5i | | (-2+x)(5x-2)= | | ys+yv=x | | 19x-5=7+13x | | 6.1x-3=5.1x | | (6cd^2+4cd)-(3cd^2-9cd^2-9cd+5)= | | 6+6q=9+5q | | c^2+6cg-27g^2=0 | | 7+(-5+4q)+(-7q-4)= |